Perbandingan Efisiensi Energi Genset Menggunakan Bahan Bakar Biogas dan LPG pada Berbagai Tingkat Beban Listrik - Hadiningrum, Kunlestiowati; Muldiani, Ratu Fenny; Pratama, Defrianto (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Biogas is an alternative energy source that is environmentally friendly, cheap, easy to obtain and renewable. In general, all types of organic materials can be processed to produce biogas, however only homogeneous organic materials (solid and liquid) such as manure and urine (urine) of livestock are suitable for a simple biogas system. Biogas can be burned like LPG and on a large scale can be used to generate electricity, so that biogas can be used as an alternative energy source that is environmentally friendly and renewable. To determine the performance of biogas as an alternative energy source, in this research the method used is to compare the performance of Biogas with LPG gas as a source of electrical energy. Analysis of trial data per minute (RPM), with varying load levels, shows that the RPM of generators using LPG only decreases slightly as the electrical load increases, which shows that the generator is able to maintain more consistent performance. The RPM produced by LPG, which ranges from 2358 to 2420 RPM, indicates that the engine is running faster and more efficiently, while biogas has a lower RPM, ranging from 1715 to 1820 RPM, which indicates slower operation. LPG efficiency ranges from 89.60% to 98.12%, while biogas efficiency ranges from 74.67% to 89.60%. Even though biogas shows less stable performance than LPG, biogas still has potential as an alternative fuel, especially in areas that have limited access to LPG but have abundant sources of biogas raw materials. The use of biogas can reduce dependence on fossil fuels and reduce greenhouse gas emissions. Even though LPG is more efficient, biogas has significant potential to be developed as a more environmentally friendly alternative energy source because LPG relies on non-renewable fossil fuels and has a negative impact on the environment in the long term.